2016
DOI: 10.1016/j.seizure.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

The potential implication of SCN1A and CYP3A5 genetic variants on antiepileptic drug resistance among Egyptian epileptic children

Abstract: Overall, results confirmed the claimed role of SCN1A c.3184 A/G polymorphism in epilepsy and moreover in development of pharmacoresistance among Egyptian epileptic children. CYP3A5*3 variants have no contributing effect on pharmacoresistance among Egyptian epileptic children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 46 publications
1
16
1
Order By: Relevance
“…This finding was confirmed by Kumari et al (68) in another study with 402 epilepsy patients from the same geographic region. Although Lakhan et al and Kumari et al did not reveal an association between SCN1A c.3184 A>G SNP and ASD resistance, Abo El Fotoh et al (69) demonstrated a significant relationship between the AG genotype or G allele and ASD resistance in Egyptian children with epilepsy.…”
Section: Potential Mechanisms Of Asd Resistancementioning
confidence: 95%
See 1 more Smart Citation
“…This finding was confirmed by Kumari et al (68) in another study with 402 epilepsy patients from the same geographic region. Although Lakhan et al and Kumari et al did not reveal an association between SCN1A c.3184 A>G SNP and ASD resistance, Abo El Fotoh et al (69) demonstrated a significant relationship between the AG genotype or G allele and ASD resistance in Egyptian children with epilepsy.…”
Section: Potential Mechanisms Of Asd Resistancementioning
confidence: 95%
“…On the other hand, the association between IVS5-91G>A in the SCN1A gene and ASD response was not observed in this study (64). Several more recent studies explored the relationship between other SNPs in the sodium channel genes and drug response in epilepsy, including SCN1A c.3184 A>G (rs2298771) and SCN2A c.56 G>A (rs17183814), both of which were found to be functionally significant in some neurological disorders (6769). In a study including 336 epilepsy patients from the northern part of India, Lakhan et al (67) reported a significant association between the variant allele frequency of SCN2A c.56 G>A SNP and ASD resistance.…”
Section: Potential Mechanisms Of Asd Resistancementioning
confidence: 99%
“…A missense mutation in SCN1A leads to dysfunction of inhibitory GABAergic neurons, resulting in brain hyperexcitability and seizures in infants [5]. Mutations in the SCN1A gene lead to severe forms of epilepsy such as Dravet syndrome, or milder forms such as generalized epilepsy with febrile seizures plus (GEFS+), simple febrile seizures and also a non-epileptic condition, familial hemiplegic migraine [6].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from their role in epileptogenesis, the voltage-gated sodium channels also play a major role as antiepileptic drug (AED) targets [6,7]. SCN1A is a target of several AEDs, with some studies demonstrating an association between the SCN1A c.3184A > G/p.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation